Microvesicles in vascular homeostasis and diseases - Ridger, Victoria C.; Lip, Gregory Y. H.; Boulanger, Chantal M.; Werner, Nikos; Shantsila, Eduard; Angelillo-Scherrer, Anne; Badimon, Lina; ten Cate, Hugo; Blanc-Brude, Olivier; Thomas, Mark; Bochaton-Piallat, Marie-Luce; Harrison, Paul; Boilard, Eric; Buzas, Edit I.; Caporali, Andreas; Dignat-George, Francoise; Evans, Paul C.; Lacroix, Romaric; Lutgens, Esther; Ketelhuth, Daniel F. J.; Nieuwland, Rienk; Toti, Florence; Tuñon, Jose; Weber, Christian; Hoefer, Imo E. (Thrombosis and Haemostasis, 2017)
Microvesicles are members of the family of extracellular vesicles shed from the plasma membrane of activated or apoptotic cells. Microvesicles were initially characterised by their pro-coagulant activity and described as “microparticles”. There is mounting evidence revealing a role for microvesicles in intercellular communication, with particular relevance to hemostasis and vascular biology. Coupled with this, the potential of microvesicles as meaningful biomarkers is under intense investigation. This Position Paper will summarise the current knowledge on the mechanisms of formation and composition of microvesicles of endothelial, platelet, red blood cell and leukocyte origin. This paper will also review and discuss the different methods used for their analysis and quantification, will underline the potential biological roles of these vesicles with respect to vascular homeostasis and thrombosis and define important themes for future research.
Keywords: Atherothrombosis; cell-cell interactions; inflammatory mediators; macrophage